Forced chromatin looping raises fetal hemoglobin in adult sickle cells to higher levels than pharmacologic inducers - Breda, Laura (Blood, 2016)
Overcoming the silencing of the fetal γ-globin gene has been a long-standing goal in the treatment of sickle cell disease (SCD). The major transcriptional enhancer of the β-globin locus, called the locus control region (LCR), dynamically interacts with the developmental stage-appropriate β-type globin genes via chromatin looping, a process requiring the protein Ldb1. In adult erythroid cells, the LCR can be redirected from the adult β- to the fetal γ-globin promoter by tethering Ldb1 to the human γ-globin promoter with custom-designed zinc finger (ZF) proteins (ZF-Ldb1), leading to reactivation of γ-globin gene expression. To compare this approach to pharmacologic reactivation of fetal hemoglobin (HbF), hematopoietic cells from patients with SCD were treated with a lentivirus expressing the ZF-Ldb1 or with chemical HbF inducers. The HbF increase in cells treated with ZF-Ldb1 was more than double that observed with decitabine and pomalidomide; butyrate had an intermediate effect whereas tranylcypromine and hydroxyurea showed relatively low HbF reactivation. ZF-Ldb1 showed comparatively little toxicity, and reduced sickle hemoglobin (HbS) synthesis as well as sickling of SCD erythroid cells under hypoxic conditions. The efficacy and low cytotoxicity of lentiviral-mediated ZF-Ldb1 gene transfer compared with the drug regimens support its therapeutic potential for the treatment of SCD.